Progression of lipase activity and pancreatic lipase immunoreactivity in dogs hospitalized for acute pancreatitis and correlation with clinical features. (5th December 2022) - Cueni, Claudia; Hofer‐Inteeworn, Natalie; Kümmerle‐Fraune, Claudia; Müller, Claudia; Kook, Peter Hendrik
Abstract: Background: Lipase activity and pancreatic lipase immunoreactivity (PLI) have not been compared in dogs hospitalized for acute pancreatitis (AP). Objectives: To describe the progression of lipase activity and PLI, and correlations with clinicopathologic features in dogs with AP. Animals: Thirty‐nine dogs with AP based on clinical signs and lipase activity >350 U/L (reference interval [RI], 24‐108 U/L). Methods: Retrospective study. Lipase activity (LIPC Roche), PLI (SpecPL), and clinical signs were recorded daily. Admission (d1) data (clinical, laboratory, and ultrasound [US] findings), and clinical signs during hospitalization (d2‐d3) were assessed for correlation with lipases. Results: Median (range) duration of clinical signs before presentation was 2 days (1‐7 days). Median (range) lipase activity and PLI at d1 were 1070 U/L (range, 357‐1500 U/L) and 1111 μg/L (range, 292‐1500 μg/L). Strong correlation between assays at d1 ( r s 0.96; P < .0001; n = 39), remained equally strong on d2 ( r s 0.964; P < .0001; n = 39), and d3 ( r s 0.966; P < .0001; n = 22). On d2, lipase activity and PLI were within RI in 13/39 (33%) and 18/39 (46%) of cases. Lipase activities were minimally increased (median, 124 U/L) in 5 dogs with d2 PLI <200 μg/L. On d3, 4 more dogs had normal lipase activity and PLI, and the nature and magnitude of change were always the same for both assays. Clinical signs were not associated with lipases. Only a hyperechoic mesentery, but not an US diagnosis of AP, correlated significantly with lipase activity and PLI. Conclusions and Clinical Importance: Lipase decreases rapidly to near or within RI within 2 days of treatment in the majority of dogs with AP. Both lipase assays yielded virtually identical results. Mesenteric echogenicity may be an early marker of AP in dogs.